Moral Teleology A Theory of Progress - Sauer, Hanno (Routledge Studies in Ethics and Moral Theory, 2023)
This book develops a unified theory of moral progress. The author argues that there are mechanisms in place that consistently drive societies towards moral improvement and that a sophisticated, naturalistically respectable form of teleology can be defended. The book's main aim is to flesh out the process of moral progress in more detail, and to show how, when the right mechanisms and institutions of moral progress are matched together, they create pressure for the desired types of moral gains to manifest. The first part of the book deals with two issues: the conceptual one about what moral progress is, and the broadly empirical one whether it is possible. It shows that cultural evolution successfully explains the origins of modern forms of morally welcome change. The second part argues that there is logical space for a moderate, scientifically credible form of teleology, and that the converse case for moral decline is weak. It addresses the types, drivers, and institutions of moral progress that allow for the storage, transmission, and cumulative improvement of our normative infrastructure over time. Finally, the third part demonstrates why moral progress cannot be accounted for in metaethically realist terms. Moral Teleology will be of interest to researchers and advanced students working in ethics, moral epistemology, and moral psychology.